INCOMPLETE PROJECT of the ENLIGHTENMENT: METHODOLOGICAL ASPECT - N. V. Golik; A. I. Izvekov (Дискурс)
A search for ways to overcome modern methodological crisis of humanitarian knowledge is one of the most urgent and pressing research challenges. Its solution, on one hand, must ensure the breakthrough of humanitaristics towards new clearly visible but still not yet developed boundaries. On the other hand, the crisis in question is so extensive that it seems there is no possibility to overcome it. The way out of the crisis to the post-crisis stage is found in a traditional way: by making a clear diagnosis. Clarification of it paradoxically allows us to find support for a methodological breakthrough in the very painful "nerve" of the crisis. Spiritual freedom of personality acquired in XX century is a notion included in textbooks but not yet incorporated into the framework of categories and concepts of modern methodology. Detailed analysis shows that this category specifically, concretized by a series of definitions, can change our perspective on the ways of overcoming the methodological crisis. In this context, the view on the Enlightenment, which methodological potential is far from being exhausted, changes significantly. Moreover, it is absolutely clear that humanity is facing the necessity and imminence of its new turn.